Sistema podgotovki sportsmenov Kanady k Olimpijskim igram - Platonov, V.; Pavlenko, I.; Tomashevskyi, V. (Science in Olympic Sport, 2018)
Objective. To analyze the system of training Canadian athletes for the Olympic Games. Methods. Analysis and generalization of scientific and documentary data.Results. The Federal Government and the Canadian Olympic Committee, national sports federations, sports training centers, provincial governments, and numerous sports organizations act as partners for the preparation athletes for the Olympic Games. The government agency Sport Canada implements its policies and takes part in shaping the Canadian sports system through these bodies. Legislative and political acts have been adopted, including position document Canadian Sport Policy, that contribute to continuous increasing of the government influence on the development of sports in Canada through the funding and monitoring mechanisms. The special program Own the Podium serves as a basis for the purposeful strategy of training Canadian athletes for the Olympic Games. Effective management structures have been established aimed at optimi zing and focusing activities of public bodies, various sports organizations, and sponsors on the training of the strongest athletes, who are really capable of stepping onto the Olympic podium. An effective policy was developed and implemented to identify the challenges of Olympic preparation, eff ective training programs for athletes were created, monitoring was planned, critical problems for scientific research were identifi ed, rapid introduction of scientific advances into practice was enabled along with the implementation of advanced world experience and advanced training coaches and other professionals. Conclusions. The formation and implementation of an eff ective system for training Canadian athletes for the Olympic Games were facilitated by: the positive attitude and support of the government for sports, physical education, and healthy lifestyle of the population; the intensive development of health enhancing physical culture and mass sports; the creation of a strong physical infrastructure; the introduction of rational organizational forms of training for top level athletes; substantial funding of Olympic preparation; and introduction of advanced technologies in all components of the training system.